Smooth versus textured tissue expanders in breast reconstruction – A retrospective review of post-operative surgical site infections. Issue 9 (September 2022) - Tevlin, Ruth; Cemaj, Sophie L.; Azad, Amee D.; Borrelli, Mimi R.; Silverstein, Max L.; Posternak, Victoria; Nguyen, Dung; Lee, Gordon K.; Nazerali, Rahim S.
Summary: Background: Textured tissue expanders (TTEs) were introduced to limit migration and reduce capsular contracture, which were inherent to smooth tissue expanders (STEs). Previous reports suggest that textured devices have increased rates of bacterial contamination and biofilm formation in comparison with smooth devices. Recently, the relative increased association of anaplastic large cell lymphoma (ALCL) with textured versus smooth devices has led to increased adoption of smooth devices. The aim of our study is to evaluate the post-operative surgical site infection (SSI) rates of STEs versus TTEs. Methods: A retrospective case series was conducted at a single academic teaching hospital from April 2016 to December 2019. The primary outcome variable was the development of a post-operative SSI. Results: One hundred seventy-seven breasts underwent reconstruction with TTEs and 109 breasts underwent reconstruction with STE. In total, 54 SSIs were recorded ( n = 34 TTE; n = 20 STE), with the majority of infections occurring within the first 30 post-operative days (TTE 65%, STE 70%). There was no statistically significant difference in overall post-operative infection rates between TTE and STE groups when broken down into the following time points: <30 day, 30–60 days, and >90 days ( p = 0.924). There was no statistically significant difference between infection type (superficial vs. deep, p = 0.932), infection management (medical, surgical, or both, p = 0.409) or salvage results ( p = 0.078) seen in STE versus TTE cohort. On multivariate analysis, seroma history was associated with SSI development (OR 3.18, p = 0.041). Conclusion: There was no significant difference in the rate of post-operative SSI following breast reconstruction with STE relative to TTE.